People with disabilities’ representation in Peru in the news of journalistic digital media in the context of COVID-19 - Medina Palpa, Gian (2023)
This research analyzed how Peru's three most-read digital newspapers (El Comercio, La República, and Trome) represented disability between March 2020 and June 2022, using a mixed-methods approach. The article reviews a sample of online news (n =300) quantitatively, through content analysis, and qualitatively by organizing discourses on disability into four types: danger, charity, integration, and social burden. When analyzing thematic sections, it was evident that the newspapers did not address disability from a political perspective and did not debate much about it. Childhood disability appeared (26.67%) in informative news pieces. Additionally, of the four identified types of discourse, the integration discourse was present in more than 50 % of the sample. Bivariate analysis showed several statistically significant intersections. For example, people with psychosocial disabilities and men are often represented as dangerous, while the charity model prevails when presenting people with physical disabilities in Trome. The results demonstrate the need to include demographic descriptors of individuals to assess disability representations properly.